1996
DOI: 10.1097/00006123-199608000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Postoperative Hearing Preservation in Patients with Acoustic Neuromas

Abstract: Postoperative long-term preservation of hearing is more likely if surgery is performed while the tumor is still small and hearing is still excellent. Under these circumstances, it is more likely that the early and late hearing loss will be compensated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…26 Changes in hearing did not correlate with tumor size, preoperative hearing, intraoperative change in hearing, the interval between initial symptoms and surgery, sex, or age in one study, 27 and hearing at long-term follow-up was significantly better in patients with excellent preoperative hearing in another study. 28 Hearing preservation proved important and realistic in our study, too, as at 5 years after surgery it remained preserved in all patients in whom it had been preserved in the early postoperative period. A significant change was noticed in 37% of patients, and specifically at higher frequencies above 1 kHz.…”
Section: Long-term Outcomesupporting
confidence: 60%
“…26 Changes in hearing did not correlate with tumor size, preoperative hearing, intraoperative change in hearing, the interval between initial symptoms and surgery, sex, or age in one study, 27 and hearing at long-term follow-up was significantly better in patients with excellent preoperative hearing in another study. 28 Hearing preservation proved important and realistic in our study, too, as at 5 years after surgery it remained preserved in all patients in whom it had been preserved in the early postoperative period. A significant change was noticed in 37% of patients, and specifically at higher frequencies above 1 kHz.…”
Section: Long-term Outcomesupporting
confidence: 60%
“…Only four patients required hearing saving operation, of whom one achieved serviceable hearing (pure-tone average º50 dB, speech discrimination score À50%). 15) Our findings suggest that the risk of tumor recurrence after NTR is quite low. Substantial adherence of the tumor to the facial nerve presents a high risk of poor facial nerve outcome.…”
Section: Discussionmentioning
confidence: 59%
“…Patients managed surgically also demonstrated varying long‐term audiologic outcomes. Umezu et al 11 reported on 73 patients managed by way of a suboccipital transmeatal approach. Of those patients, 51 demonstrated preoperative hearing that was Gardner‐Robertson class 3 or better.…”
Section: Discussionmentioning
confidence: 99%
“…Of those patients, 51 demonstrated preoperative hearing that was Gardner‐Robertson class 3 or better. After surgery, only 21 (41.2%) of the 51 patients retained class 1 to 3 hearing 11 . Kaylie et al 12 reported hearing outcomes on 97 patients who underwent tumor excision.…”
Section: Discussionmentioning
confidence: 99%